2019
DOI: 10.1126/science.aax3442
|View full text |Cite
|
Sign up to set email alerts
|

Neonicotinoids disrupt aquatic food webs and decrease fishery yields

Abstract: Invertebrate declines are widespread in terrestrial ecosystems, and pesticide use is often cited as a causal factor. Here, we report that aquatic systems are threatened by the high toxicity and persistence of neonicotinoid insecticides. These effects cascade to higher trophic levels by altering food web structure and dynamics, affecting higher-level consumers. Using data on zooplankton, water quality, and annual fishery yields of eel and smelt, we show that neonicotinoid application to watersheds since 1993 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
111
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(124 citation statements)
references
References 20 publications
2
111
1
1
Order By: Relevance
“…Due to their high water solubility, there have been growing concerns about their potential risks to the aquatic environment. For example, a recent study revealed that neonicotinoid application to watersheds since 1993 coincided with an 83% decrease in the average zooplankton biomass in spring ( Yamamuro et al 2019). Neonicotinoids used in agricultural fields can contaminate the aquatic environment such as rivers via the soil and subsurface water.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their high water solubility, there have been growing concerns about their potential risks to the aquatic environment. For example, a recent study revealed that neonicotinoid application to watersheds since 1993 coincided with an 83% decrease in the average zooplankton biomass in spring ( Yamamuro et al 2019). Neonicotinoids used in agricultural fields can contaminate the aquatic environment such as rivers via the soil and subsurface water.…”
Section: Introductionmentioning
confidence: 99%
“…However, few precursive safety tests were performed on beneficial insects, for which neonicotinoids are now known to be potent neurotoxins with well-documented lethal and sub-lethal effects 11,15,17,18,19 . Therefore, continued intensive use is likely to have severe consequences on insect species numbers, with knock-on effects for the ecosystem, aquatic life, birds and mammals in addition to potential toxicity to humans 11,[20][21][22] . Despite the recent European Union (EU) ban of three major neonicotinoids (the nitroimines: imidacloprid, clothianidin and thiamethoxam, the latter being a prodrug for clothiandin 23 ), neonicotinoids remain the most widely used class of insecticide globally, with a number of studies showing there has been no decrease in the quantity of banned neonicotinoids found in different populations of honey and bumble bee across Europe a year after the ban 24,25 .…”
Section: Introductionmentioning
confidence: 99%
“…In that same year,a rthropod populationsc ollapsed, leading to changes in food sourcesw ith dramatic falls in the numberso f two commercially harvested freshwater fish by the end of 1994;t hese speciesh ave never recovered. [41] Environmental breakdown products such as desnitroimidacloprid (Figure 1) have ah igh affinity for mammalian nAChRs and are highly toxic to mice. [42] Imidacloprid administration at field-relevant doses in drinking water affects white tail deer and fawns.…”
Section: Resultsmentioning
confidence: 99%